STRENGTHENING THE ROLE OF ISLAMIC PAWNSHOP IN ISLAMIC FINANCING FOR MSMES: ANP APPROACH - Lydia Edgina; Thuba Jazil; Tita Nursyamsiah (Institute for Research and Community Empowerment (LPPM TAZKIA), 2016)
Objectives: aims to strengthen the role of Islamic pawnshop in financing for Micro Small & Medium EnterprisesMethods: analytic network process (ANP) approachResults: the main problem of Islamic pawnshop in expansion was its internal. The most priority was on socialization through promotion and advertisement. The appropriate strategy to be executed was marketing strategy to expand Ar-Rum product (financing for MSMEs) through sales marketing.Conclusion: the considered action was massive socialization to the societies using effective and efficient marketing strategy.